The first one hundred cases of tetralogy of Fallot admitted to Hacettepe Children's Hospital - Ertuğrul, Ali (The Turkish Journal of Pediatrics, 1962)
Common findings and symptoms in 100 selected cases of tetralogy of Fallot are presented together with the results of electrocardiographic, roentgenographic and angiocardiographic studies. Operative results in 50 cases are discussed and it is suggested that the Blalock operation, in preference to the Potts, may become the operation of choice in such cases in future.